IMPORTANCE OF THE INCLUSIVE REPORTING IN THE PROCESS OF CIVIL INTEGRATION OF PERSONS WITH DISABILITIES (GEORGIAN PUBLIC BROADCASTER FIRST CHANNEL, 2021) - Lia Zambakhidze; Nino Chalaganidze (International Journal of Innovative Technologies in Social Science, 2023)
Clearly formed attitudes based on the morality and law force any citizen to respect, to recognize individualism of each person, his uniqueness and equality. Establishing of a kind of society having such democratic values and reaching of an absolute equality remains to be a key challenge in any country. Particularly, it refers to the persons with disabilities, as resolving of the given task requires overcoming of a physical resistance on top of the morality. “We are tired of being statistics, cases, wonderfully courageous examples to the world, pitiable objects to stimulate fund-raising”. (Hunt, 1966, p. 4) Reassessment of the attitudes implemented in the society is majorly guaranteed by the inclusive reporting with its specifics and characteristics. The present research, based on the example of the Georgian Public Broadcaster – First Channel demonstrates specifics of providing of the audience with the issue in a very delicate form. Legal and ethical levers, practical experience of media outlets are represented in it. In addition to the stated, ways of inclusive representing are discussed, being a method of revealing of significance and priority of the persons with disabilities.